Teste de tetrazólio em sementes de jucá (Libidibia ferrea (Mart. ex Tul.) L.P. Queiroz var. ferrea) - Carvalho, Sara Monaliza Costa (2016)
Currently, the most widely used test for assessing the seed physiological quality is the germination. However, this presents some obstacles, the largest one, is a long time to obtain results, especially for forest species. The tetrazolium test provides fast results, and this has proved to be a promising alternative for the determination of viability of this kind of seed. However, the success of the test depends on the development of an appropriate methodology for each species. Thus, this research aimed to evaluate procedures for the pre-wetting, preparation and staining jucá seeds to tetrazolium test. The experiments have been divided into two steps. As in the first trial were tested pre-wetting conditions and seed preparation, the second was dedicated to the dyeing stage, in which three concentrations of tetrazolium solution were tested (0.05, 0.075 and 0.1%) and three periods (1, 3 and 6 hours) at the temperatures of 35 to 40 ° C. The seeds were sorted into viable or non-viable according to the colorations obtained. At the same time, the germination test was conducted to compare the results with the feasibility estimates by the tetrazolium test. It was found that the mentioned test is efficient to evaluate the feasibility of jucá seeds and to implement it is recommended the scarification of the seeds with sandpaper followed by soaked paper towel for 42 hours at 25 ° C and removal of the seed coat, with subsequent immersion of the seeds into the tetrazolium solution at 0.05% for 3 hours at 35 or 40 ° C